Towards a Vaccine Against Rheumatic Fever - L. Guilherme; K. C. Faé; F. Higa; L. Chaves; S. E. Oshiro; S. Freschi de Barros; C. Puschel; M. A. Juliano; A. C. Tanaka; G. Spina; J. Kalil (Clinical and Developmental Immunology)
Rheumatic fever (RF) is an autoimmune disease which affects more than 20 million children in developing countries. It is triggered by Streptococcus pyogenes throat infection in untreated susceptible individuals. Carditis, the most serious manifestation of the disease, leads to severe and permanent valvular lesions, causing chronic rheumatic heart disease (RHD). We have been studying the mechanisms leading to pathological autoimmunity in RF/RHD for the last 15 years. Our studies allowed us a better understanding of the cellular and molecular pathogenesis of RHD, paving the way for the development of a safe vaccine for a post-infection autoimmune disease. We have focused on the search for protective T and B cell epitopes by testing 620 human blood samples against overlapping peptides spanning 99 residues of the C-terminal portion of the M protein, differing by one amino acid residue. We identified T and B cell epitopes with 22 and 25 amino acid residues, respectively. Although these epitopes were from different regions of the C-terminal portion of the M protein, they showed an identical core of 16 amino acid residues. Antibodies against the B cell epitope inhibited bacterial invasion/adhesion in vitro. Our results strongly indicated that the selected T and B cell epitopes could potentially be protective against S. pyogenes.